(3Odjd GdeMbbjf hGdHGMKjf aj JMbjbGJge hCHMGKge (B/s - (3GdYWjI, eQhGfs ((3GdQjGV (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s (3OGQ GdYdG ddfTQ hGdJhRjY ,s, 2014)
(3jJfGhd cJGH (B((3Odjd GdeMbbjf hGdHGMKjf aj JMbjbGJge hCHMGKge(B) (3hGdPj bGe HJCdjag GdOcJhQ (B"(3eQhGf GdYWjI(B" (3cjajI fbO GdfUhU hJMbjb GdeNWhWGJ, MjK jYJHQ ef GdYdhe GdgGeI ddHGMKjf hGdeMbbjf aj eSjQJge GdYdejI, hfbSe GdcJGH Edi HGHjf QFjSjjf (B: (3GdHGH GdChd (B: (3aj GdJMbjb, hjTJed Ydi aUhd NeSI (B: (3GdChd (B: (3QSGdI Yf JdGbM GdMVGQGJ, GdKGfj (B: (3YdGeGJ GdJQbje hGdQSe GdEedGFj, GdKGdK (B: (3GdJMbjb YfO GdeSJTQbjf hGdYQH, GdQGHY (B: (3GdcdGe Ydi GdfSN GdNWjI, GdNGeS (B: (3UaGJ GdeMbb hGdELQGAGJ GdYedjI ddJMbjb, hGdHGH GdKGfj (B: (3aj GdHMK, hjTJed Ydi NeSI aUhd (B: (3GdChd (B: (3efGgL GdHMK heUWdMGJg hWQjbI GNJjGQ GdHMK, GdKGfj (B: (3egeI GdHGMK hUaGJg hKbGaJg hecJHJg, GdKGdK (B: (3bhGYO EYOGO GdHMK hcJGHJg, GdQGHY (B: (3CHMGK GdOQGSGJ GdYdjG hGdeGLSJjQ hGdOcJhQGg, GdNGeS (B: (3GSJNOGe GdMGSH GdBdj heOi GdGSJaGOI ef GdEfJQfJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B411-416.s
Keywords: (3GdeNWhWGJs -- (3JMbjb GdeNWhWGJs; (3GdeYQaIs -- (3GdHMKs -- (3EYOGO GdHMhKs